When pain is not a place: Pain and its metaphors in late middle English medical texts - Díaz Vera, Javier Enrique (Onomázein, 2012)
In this research i will identify and describe the metaphorical expressions for pain recorded in the texts included in the Middle English Medical Texts corpus, a collection of english medical writings from the period 1350- 1500. Furthermore, i will propose a comparison between the resulting list of specialised medical metaphors and a list of metaphorical patterns for pain extracted from a multi-genre, late middle english corpus, the Helsinki Corpus of English Texts (subperiods me iii and me iV), which i will use here as my reference corpus. in doing so, i will try to show that medieval medical authors borrowed or developed new metaphorical extensions in order to describe pain and its treatments. Through the use of these metaphorical patterns, medieval medical writers tried to refer to pain as a process, with a beginning, a treatment and an end. in fact, pain is frequently conceived of as a living entity of adverse nature (e.g. a soldier, an enemy, a wild animal), and it is the doctor’s role to fight it with all the weapons (i.e. treatments) at his disposal. These conceptual choices differ greatly from the conceptualizations of pain found in the multi-genre corpus, where pain is frequently conceived of as a permanent state or as a place.